Follicular B-Cell Lymphoma Embedded in a Pulmonary Chondroid Hamartoma: A Case Report - Lara Mannelli; Sofia Kovalchuk; Benedetta Puccini; Gemma Benelli; Catia Dini; Alberto Bosi; Luigi Rigacci (Archives of Hematology Case Reports and Reviews - Peertechz Publications, 2017)
Background: Here we report a rare case of concomitant pulmonary chondroid hamartoma and follicular non Hodgkin lymphoma in a 65-year-old woman with a history of 4-month nonspecific symptoms like fever, sweating and weight loss. Methods: Chest CT scan revealed a 12-mm nodule with relatively regular margins in the right middle lung field, adhering to the chest wall, with no involvement of hilar or mediastinal lymph nodes. The patient underwent thoracoscopy and resection of the lesion. Following histological exam and immunohistochemical staining, the patient was diagnosed as having follicular b-cell lymphoma embedded in a pulmonary chondroid hamartoma. FISH analysis was performed and showed the presence of typical follicular lymphoma chromosomal translocation t (14;18) (q32;q21). Conclusions: Following the final diagnosis, we decided not to refer the patient to chemotherapy and she enter watch and wait regimen with imaging control every 6 months. After 18 months, the chest X-ray and abdominal ultrasound are still negative with no evidence of recurrence.